Copper-Graphene-Based Photonic Crystal Fiber Plasmonic Biosensor - Ahmmed A. Rifat; G. Amouzad Mahdiraji; Rajib Ahmed; Desmond M. Chow; Y. M. Sua; Y. G. Shee; F. R. Mahamd Adikan (IEEE Photonics Journal, 2016)
We propose a photonic crystal fiber surface plasmon resonance biosensor where the plasmonic metal layer and the sensing layer are placed outside the fiber structure, which makes the sensor configuration practically simpler and the sensing process more straightforward. Considering the long-term stability of the plasmonic performance, copper (Cu) is used as the plasmonic material, and graphene is used to prevent Cu oxidation and enhance sensing performance. Numerical investigation of guiding properties and sensing performance is performed by using a finite-element method. The proposed sensor shows average wavelength interrogation sensitivity of 2000 nm/refractive index unit (RIU) over the analyte refractive indices ranging from 1.33 to 1.37, which leads to a sensor resolution of $5× 10^{-5}\ \text{RIU}$ . Due to the simple structure and promising results, the proposed sensor could be a potential candidate for detecting biomolecules, organic chemicals, and other analytes.